“Zambia Shall be Saved!”: Prosperity Gospel Politics in a Self-Proclaimed Christian Nation - Haynes, Naomi (Nova Religio: The Journal of Alternative and Emergent Religions, 2015)
This article explores the increasingly common argument that Pentecostal Christianity, far from being apolitical, is very politically engaged. I make two contributions to this discussion. First, my analysis provides a detailed account of how Pentecostal religious life serves as political engagement in an especially significant ethnographic context: Zambia, the only African country to make a constitutional declaration that it is a “Christian nation.” For Zambian Pentecostals, “the declaration” is a covenant with God made according to the principles of the prosperity gospel. By regularly reaffirming that covenant through prayer, believers do political work. My treatment of the prosperity gospel represents the second contribution of this article. Whereas others have argued that the prosperity gospel undermines public engagement, I show how its practices inform the political efforts of Zambian believers. I conclude by reflecting on how changes in the prosperity gospel may shape the future political actions of African Pentecostals.
free